Evaluasi Kerangka Konseptual Daya Dukung Ekowisata (Studi Kasus: Taman Nasional Karkheh dengan Taman Nasional Indonesia) - Fransisca Rimbunita Salusu; Ayang Khairunnisa; Affrida Amalia; Naufalika Anggi Zidany; Teten Febriawan; Alhilal Furqan (JURNAL NASIONAL PARIWISATA, 2023)
Carrying capacity measurement in an ecotourism concept is very important to measure the capacity of space to receive the number of tourists and their activities in the area. The calculating methods of the carrying capacity concept have been implemented in several ecotourism areas based on several categories, such as; physical, real, effective, ecological and socio-cultural carrying capacity. In this case, research was carried out with the aim of studying the concept of carrying capacity applied in Karkheh National Park and National Parks in Indonesia. This can be studied to find a new concept that can be useful for carrying capacity calculations in Indonesia which are more complex and on target. Literature study is the method used in this research to examine information related to each National Park area. Thus, the results of the elaboration of the concept of carrying capacity between Karkheh National Park and National Parks in Indonesia show that socio-cultural carrying capacity needs to be applied to National Parks in Indonesia because of the same high density context.